Hearing Loss Caused by HCMV Infection through Regulating the Wnt and Notch Signaling Pathways - Sheng-Nan Huang; Yue-Peng Zhou; Xuan Jiang; Bo Yang; Han Cheng; Min-Hua Luo (Viruses, 2021)
Hearing loss is one of the most prevalent sensory disabilities worldwide with huge social and economic burdens. The leading cause of sensorineural hearing loss (SNHL) in children is congenital cytomegalovirus (CMV) infection. Though the implementation of universal screening and early intervention such as antiviral or anti-inflammatory ameliorate the severity of CMV-associated diseases, direct and targeted therapeutics is still seriously lacking. The major hurdle for it is that the mechanism of CMV induced SNHL has not yet been well understood. In this review, we focus on the impact of CMV infection on the key players in inner ear development including the Wnt and Notch signaling pathways. Investigations on these interactions may gain new insights into viral pathogenesis and reveal novel targets for therapy.